A90 SCREENING FOR COMORBID SERONEGATIVE ARTHRITIS AND INFLAMMATORY BOWEL DISEASE IN AN AMBULATORY GASTROENTEROLOGY AND RHEUMATOLOGY PRACTICE MODEL. (15th March 2019) - Bollegala, N; Gakhal, N; Marani, H; Chu, C
Abstract: Background: The most common extra-intestinal manifestation of inflammatory bowel disease (IBD) is arthritis with a prevalence of 17–39%. Two thirds of patients with seronegative spondyloarthropathies show histologic signs of gut inflammation, and some of these patients go on to develop clinical symptoms of IBD. Though the frequency of bowel and joint symptoms in the respective diseases has been well published there is no data that shows how frequently these symptoms are screened for and the extent of screening. This is important knowledge as the identification of comorbid disease may have a critical impact on initiation of therapy and reduction in disease related morbidity. Aims: The objective of this study was to determine the frequency and type of screening for bowel and joint symptoms in outpatient rheumatology and gastroenterology (GI) clinics in an academic ambulatory hospital. Methods: A retrospective cohort study was performed using data from a sample of gastroenterology (n=221) and rheumatology (n=172) patients recorded in the electronic medical record between January 1, 2015 and December 31 2017. Data was extracted between February 1st, 2018 and May 31st, 2018. Data on patient characteristics, disease type, medications and presence and method of screening was manually extracted data from each patient's electronic chart. Chi-square tests of independence were conducted to assess the distribution of patient and provider baseline characteristics based on screening status. Multivariate logistic regression was used to investigate the likelihood of being screened while adjusting for baseline characteristics. Time to screening from first visit was measured using a Kaplan-Meier survival analysis. Results: In rheumatology, 87.8% of patients were screened for GI symptoms. Age, type of arthritis, and medications did not affect screening rates. Providers who were in practice longer tended to screen less frequently (16.4 vs 13.5 years p value = 0.0003). In GI, only 16.3% of patients were screened for joint symptoms. Age and medications did not affect screening rates, however patients with a history of ulcerative colitis tended to be screened less frequently (77.8% not screened, p value = 0.0059). A history of any extra- intestinal manifestation of IBD increased screening rates (77.8% screened p value < 0.0001) and providers who were in practice longer tended to screen less frequently (9.5 vs 5.1 years, p value < 0.0001). Conclusions: There exist patient and provider characteristics that predict screening rates for comorbid conditions in GI and rheumatology. This baseline data will be used to develop a quality improvement intervention to improve screening rates in both populations. Funding Agencies: Department of Medicine, Women's College Hospital